HUBUNGAN KEMAMPUAN MANAJERIAL KEPALA SEKOLAH, STRES DAN ETOS KERJA TERHADAP KOMITMEN GURU - Abas, Ibnu; Bahri, Saiful; Rasyid, Suparta (Universitas Islam Negeri Sumatera Utara Medan, 2024)
The aims of this research are (1) to determine the relationship between the managerial abilities of school principals and the commitment of State Middle School teachers in Meureubo District, West Aceh Regency (2) To determine the relationship between work stress and the commitment of State Middle School teachers in Meureubo District, West Aceh Regency (3) To determine the relationship work ethic towards the commitment of State Middle School teachers in Meureubo District, West Aceh Regency. (4) To determine the relationship between school principals' managerial abilities, stress and work ethic on the commitment of State Middle School teachers in Meureubo District, West Aceh Regency. This research uses quantitative methods, a quantitative descriptive approach. This research is a population study that uses a research sample of 83 people, the sampling technique is total sampling. Likert scale questionnaire data collection techniques and data processing techniques for multiple linear regression analysis. Partial research findings obtained (1) there is a positive and significant relationship between the managerial ability of school principals and teacher commitment with a significant value of 0.001. (2) There is a positive and significant relationship between stress and teacher commitment with a significant value of 0.0031. (3) There is a positive and significant relationship between work ethic and teacher commitment with a significant value of 0.0001. Research findings simultaneously showed that there was a positive and significant relationship between the managerial ability of school principals, stress and work ethic on the commitment of State Middle School teachers in Meureubo District, West Aceh Regency with a significant value of 0.0000. The findings of this research have practical implications, namely providing awareness and input to related agencies and teachers, that in these agencies there is a problem that will affect various aspects therein, such as ineffective learning processes, lack of teacher commitment to the school, and so on. -other. From these problems, agencies can provide solutions to problems that occur in their agencies. It is hoped that suggestions to schools through this research can become a reference in making various policies in school principal management and decisions so that they can reduce teacher work stress in the school and improve the teacher's work ethic well, thus having an impact on increasing teacher commitment in the school.